International Technical Digest on Electron Devices Meeting 1992
DOI: 10.1109/iedm.1992.307403
|View full text |Cite
|
Sign up to set email alerts
|

A MOSFET with Si-implanted gate-SiO/sub 2/ insulator for nonvolatile memory applications

Abstract: A MOSFET with Si-implanted gate-SiO, insulator (MEmory-Insulator Transistor MEIT) is fabricated and investigated, especially with emphasis on its feasibility. for nonvolatile memory applications for the first time. A highdose Si' implantation to thermal SiO, introduces excess-Si cites acting as traps responsible for a memory effect. 14s a result, a large Vr window of -10 V is achieved by applying small electric fields of 3-5 MV/cm to the MEIT insulator fof write/erase programming. By taking advantage of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Metal nanocrystals can be utilized for the fabrication of nonvolatile memory devices by making use of localized trap sites, due to their remarkable properties including the Coulomb blockade effect and the controllable size [1,2]. The nanocrystals are embedded as charge-storage nodes between a control oxide layer and a tunneling oxide layer in order to replace continuous floating gate layers used in conventional flash memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanocrystals can be utilized for the fabrication of nonvolatile memory devices by making use of localized trap sites, due to their remarkable properties including the Coulomb blockade effect and the controllable size [1,2]. The nanocrystals are embedded as charge-storage nodes between a control oxide layer and a tunneling oxide layer in order to replace continuous floating gate layers used in conventional flash memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…This shows the annealing behavior of nanocrystals in an 8 nm thick SiO 2 on Si after implantation with 1 keV Si ions to a fluence of 2 Â 10 15 Si cm À2 . This is an important consideration for nonvolatile memory (NVM) applications where the nanocrystals are charged and discharged by electron tunneling to the substrate [29]. A separate study has shown that the width of such denuded zones can be controlled by suitable choice of the implantation and annealing conditions [28].…”
Section: Effect Of Surfaces and Interfacesmentioning
confidence: 99%
“…The combined interface trap charge per cycle Qss is given by (17) where &(=lo4 cm') is the gate area of MOSFET, v*(=107 cm/s) is the thermal verocity, 0,(=6.5xlO-~~ cm2) and a,(=2.4~10-'~ cm2) are the capture cross sections of electron and hole, AV,(= 6V) is the pulse amplitude, a(= 0.5) is the fraction of the rise time [26],According to (16) and (17), a mean interface trap density D,, distributed between V, and V, can be extracted by the measurement of charge-pumping current Im.…”
Section: -3 Charge Pumping Methods (M) [ I 02526]mentioning
confidence: 99%
“…The Si-implantation was selected because it produces traps and states in the SiOz and/or SiOz-Si interface, and affects the current-voltage (I -V) curves in heavy dose cases [12-141. Furthermore, MOSFETs with heavy Siimplanted SiOz exhibit hysteresis in the I -V curve due to the trap-like behavior of excess Si atoms and offer a possibility of a non-stacked EEPROM or flash memory [15][16][17]. Recently, it was reported that the Si-implanted MOS capacitor exhibited visible electro-luminescence and might be useful for a light emitting device which has process compatibility with Si LSIs [18, 191. However the effects of heavy Si implantation into the gate-SiOz on Dit have not been extensively studied until now.…”
Section: Introductionmentioning
confidence: 99%